2021
DOI: 10.1029/2020ea001482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chinese Scatterometer Ocean Surface Wind Data: Preliminary Analysis

Abstract: The qualities of wind products under different atmospheric stratification conditions are also evaluated. The results reveal that the order of retrieved wind quality from high to low can be ranked as HY-2B/SCAT, CFOSCAT and HY-2A/SCAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is expected to provide more robust results from the RFM method. Currently operating missions are HY-2B and HY-2C (Haiyang satellites) with the HSCAT scatterometer instrument onboard launched by the Chinese National Satellite Ocean Application Service (NSOAS) (Zhao et al (2021)). The China-France Oceanography Satellite CFOSAT satellite with a scatterometer launched by Centre National d'Etudes Spatiales (CNES)…”
Section: Data Sampling Characteristicsmentioning
confidence: 99%
“…This is expected to provide more robust results from the RFM method. Currently operating missions are HY-2B and HY-2C (Haiyang satellites) with the HSCAT scatterometer instrument onboard launched by the Chinese National Satellite Ocean Application Service (NSOAS) (Zhao et al (2021)). The China-France Oceanography Satellite CFOSAT satellite with a scatterometer launched by Centre National d'Etudes Spatiales (CNES)…”
Section: Data Sampling Characteristicsmentioning
confidence: 99%
“…At the same time, rainfall causes backscattering attenuation, which affects data accuracy [6][7][8]. Nevertheless, HY-2B data have demonstrated superior quality compared to that of other products in its class [9][10][11] and have been utilized in various applications. In some studies on data applications, HSCAT-B data have shown good application value.…”
Section: Introductionmentioning
confidence: 99%
“…After the launch of satellite-borne satellite sensors, verification of data products is an essential procedure (Bailey & Werdell, 2006;Ye et al, 2015). Multiple data sources including satellite or buoy data are employed to validate CFOSAT SCAT wind field measurements, revealing a strong agreement between the inversion results of SCAT winds and satellite or buoy observations (Dong et al, 2020;Ye, Li, et al, 2021;Zhao et al, 2021). The root mean square error (RMSE) for wind speed measurement was below 1.5 m/s, while the measurement error for wind direction was less than 15°, indicating that the overall quality of the wind field has attained an advanced level.…”
Section: Introductionmentioning
confidence: 99%